Design and Development of Sustainable Construction Strategy for Residential Buildings: A Case Study for Composite Climate - Dhanjode, Chetan S; Ralegaonkar, Rahul V; Dakwale, Vaidehi Aniket (International Journal of Sustainable Construction Engineering and Technology, 2013)
Developing cities in India like Nagpur are growing exponentially in population due to industrialization. The ever increasing demand of the natural resources leads to depletion of limited resources and also affects local environment in terms of increasing pollution emissions especially carbon emission. With recourse to composite climatic condition (Nagpur, India) the sustainable construction strategy is developed in the present paper. The developed strategy includes conservation of soil, energy, resources, material and water. It provides a systematic approach towards sustainability of building through quantification of energy consumption. Analysis of conventional and non-conventional material and technology on cost, energy consumption and carbon emission parameters helps in highlighting suitable options for sustainable construction. Strategy is validated through a case study of new construction of the residential buildings for enhanced environmental performance. The amount of excavated soil and its reutilization on site is taken into consideration. Locally available sustainable construction materials are compared for material cost, and embodied energy for selection of appropriate construction material. In order to conserve the ground water various options for the low flow devices, roof top rainwater harvesting and gray water recycling and reuse are suggested. Application of sustainable construction strategy to case study building revealed that 97% of natural soil is conserved through backfilling. Estimated carbon emission reduction due to recommended construction materials (sustainable bricks, cement, and steel) with respect to conventional options is of the order of 60%. Recommended water conservation options resulted in 57% reduction in ground water demand. However suggested sustainable construction strategy options estimated in increase in project cost by 13% whose effect can subsequently be reduced over the design life span computations. The developed strategy can further be applied to the larger residential township areas with varying building types for conserving the natural resources as well as reducing the impact of environmental pollution.